Preliminary PCR Screening and Optimization for Five Suspected Viruses in Haemaphysalis bispinosa Ticks from Moa Buffalo (Bubalus bubalis) - Prasetyarti Utami; Rony Marsyal Kunda (Postgraduate, University of Mataram, 2026)
Tick-borne viruses are becoming a serious threat to livestock health, especially in tropical regions where monitoring systems are still limited. H. bispinosa, the main external parasite of water buffalo in Eastern Indonesia, is suspected of carrying several veterinarians' important viral pathogens. This study aims to detect five viruses consisting of DNA viruses (BuGyKV, BoHV-1, and OvHV-2) and RNA viruses (FMDV and TAMV). FMDV and TAMV, both RNA viruses, need to be converted into complementary DNA (cDNA) through reverse transcription, which is then used as a template for PCR amplification using virus-specific primers. All viruses were detected using specific primers and extensive annealing temperature optimization. The results showed weak and nonspecific amplification bands at one temperature for BuGyKV, BoHV-1, and OvHV-2, but these bands did not match the expected amplicon size. No amplification bands were observed for FMDV and TAMV under any conditions. These findings suggest that this amplification failure is likely due to primer mismatch with local virus variants resulting from geographical differences. Overall, it can be concluded that the five target viruses were not detected in the H. bispinosa samples examined. This preliminary study provides an initial virological overview of H. bispinosa ticks from Moa Island and emphasizes the need for more sensitive detection methods, such as nested PCR, qPCR, or metagenomic approaches, to improve the detection of low-titer viruses in ticks.